PEMBERIAN PUPUK ORGANIK BIO-SLURRY PADAT PADA TANAMAN PAKCHOY (Brassica chinensis L.) - Alfred Klinton M; Agus Sutikno; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research is aimed to get the dosage of bio-slurry organic fertilizer solid suitable for growth and production of pakchoy plants. The research was conducted in Experimental Field of Faculty of Agriculture, University of Riau. The soil type used is Inceptisol. The study was conducted for three months starting from July to October 2016. The experiment was conducted experiments using Completely Randomized Design (RAL), which consisted of 5 treatments and 4 replications. The total experimental unit was 20 plots, with each plot contained 16 plants. Each plot was taken 4 randomly sampled plants. The observational data were analyzed statistically using Analysis of Varian (ANOVA), and Duncan Multiple Range Test at the 5% level. The observed parameters consist of plant height, leaf number, fresh weight of plant, fresh weight of plant worth consumption, root volume, shoot-root ratio and dry weight of the plant. The results showed that the treatment of bio-slurry organic fertilizer solid can increase plant height, leaf number, fresh weight of plant, fresh weight of plant worth consumption, root volume and dry weight of the plant. The best treatment for the production of pakchoy plants are bio-slurry organic fertilizer solid with a dose of 2000 g/plot (20 tons/ha).  Keywords: bio-slurry, organic fertilizer, pakchoy